Les statistiques coloniales en question. Niveaux de vie, croissance démographique et économie des populations indigène et européenne en Algérie au xixe siècle. Approche par l’histoire anthropométrique - Laurent Heyberger (Les Cahiers de Framespa)
The data processing of French colonial military archives makes it possible to reconstitue the changes in mean height of colonial recruits (spahis and tirailleurs) and European conscripts of Algeria, respectively for birth decades 1800-1880 and 1850-1880. Stature, considered as an index of net nutrition, brings to question the socio-economic history and the demographic history of 19th-century-Algeria : the burden of the invasion war, the balance sheet of the demographic disaster of 1867-1868 and the reality of the demographic growth after 1871 for indigenous people, the nutritional balance sheet of colonization for the European population of Algeria. Confronting stature to other indexes (rainfall, food availabilities, populations censuses, etc.) brings to revalue the Algerian population of 1830 to at least 4.2 millions inhab.